Possibilities of Using Prefabricated Modular Panels for Building NZEB Buildings in Earthquake-Affected Areas in Croatia – Case Study - Begic, Hana; Krstic, Hrvoje (International Journal of Sustainable Construction Engineering and Technology, 2022)
This case study questions the possibility of using the prefabricated modular panels for building nZEB homes in earthquake-affected areas in Croatia. The comparison of the traditional and prefabricated construction was made in terms of construction costs and time, and energy consumption. Four cases of a ground floor family house were simulated in this research: two using modular prefabricated panels and two built traditionally with hollow brick. The energy consumption of all houses was compared to the current Croatian nZEB requirements. Furthermore, the costs, durability, and construction time of prefabricated and traditionally built houses were compared. The results showed that although prefabricated houses consume less energy, and experience lower thermal losses, they are slightly more prone to overheating in the summer. Finally, it was concluded that prefabricated houses are the best solution for current earthquake-caused situation due to their construction time which is significantly shorter compared to the traditionally built houses.